(untitled) (American Journal of Islam and Society, 1996)
The stars tremble in their courses over man’s upward march lest this fallen star should become the perfect moon!’ The central question this article addresses is whether human beings can act creatively. I shall first tackle the related question of how God’s creativity is distinguished from that of humanity and then move on to the more complex question of the nature of human creativity. God’s Creativity is Different from That of Humankind The Qur’an relates rubb (lord) to khalq (creation): He said: “Our Lord [rubb] is He who gives to everythmg its . . . [khalq] . . . and further gave (it) guidance. (Qur’an 20:50)’ The noun khalq is considered by lexicographers to be derived from the root verb khaluqu (to create, to make, to originate). And if God (ul Khaliq) created or orignated, then khalaqa is a verb that signifies His creative ability. According to al Raghib, khalq is used to describe the creativity (ibda) of a thing without imitation (ikhtiza’): He assigns this role of khulq to God (al Khaliq). For a1 Tabataba‘i “the God of the universe is one, He alone created and He alone manages it.“ In fact, the link between God as rabb and khalq is accentuated by al Tabari, who considers rubb to be “the owner to whom the creation . . . belongs.’“ Moreover, this...